Percepção dos idosos da 4ª idade acerca do processo de envelhecimento - MARINS, Josafá Barbosa (2019)
The aging of the population is a phenomenon present in society, caused by the improvement in access to health services and quality of life. The longevity arises as a result of this process and stands out the growth of the population with 80 or more years, known as the 4th age. Understanding how the elderly perceive this aging is fundamental to planning actions aimed at the real needs of this group. The aim of this study is to understand the perception of elderly people about the aging process. A qualitative study was carried out, where 32 elderly people aged 80 years or older who were in care at the Center for Comprehensive Care for the Elderly - CAISI, of both sexes, were interviewed who were holders of physical and cognitive capacity and allowed interaction with the researcher.Used as a research instrument a questionnaire that allowed characterizing the sociodemographic profile of the participants and the interview. The data was collected and organized into spreadsheets of the Microsoft Office Excel® 2013 for Windows 2010 program already with automatic conversion of scores and performed calculations of Average and Median. After transcription of the texts of the interviews to the computer, exhaustive readings were made to establish categories that can express the report of the elderly. The speeches were not altered or corrected with regard to accentuation and grammar. The information processing occurred through the categorial content analysis. The steps to be followed are: Pre-analysis, consisting of floating reading, which will allow us to make exhaustive contact with the material collected. Following the constitution of the corpus, the material was organized in order to answer questions of validity, such as completeness, representativeness, homogeneity and relevance. In this phase, the recording units (phrases), the hypotheses, the theoretical framework in which the results will be analyzed, the cut-outs and the categorization form were determined; Exploitation of the material where it was subjected to categorization operations. Of the participants, 68% were male, between 80 and 90 years old (53%), blacks (40%), married (53.13%) and cohabiting with children (46%). After analyzing the interviews the following categories emerged for discussion: Intentions and experiences of the aging process, Social institutions and the aging process and Meanings attributed to aging. It is important to understand the aging process as a tool for the reconstruction of public policies and as a guide to decision-making by professionals able to meet the real needs of this population group. Reflecting on the perception of aging, from the discourses of the elderly of the elderly, is a way to understand this new look about aging, given that the perception of the elderly may vary according to the socioeconomic and cultural group to which it is linked .